Creating Reality: How Television News Distorts Events - Kline, Stephen (Canadian Journal of Communication, 1979)
Creating Reality is one of a group of recent books motivated by the perception that the increasing power of television news in defining the reality for the American public is a crucial social issue. The well-documented dependency of the public on TV news for information about events in the world, and the credibility with which the audience regard this coverage, have drawn a number of authors' attention to that group of people who act in their various journalistic capacities as the information gatekeepers of the nation and to the process of news production.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjE5Nzl2NW4zYTIwOA